Experimental characterization of speech aerosol dispersion dynamics - Zu Puayen Tan; Lokesh Silwal; Surya P. Bhatt; Vrishank Raghav (Scientific Reports, 2021)
Abstract Contact and inhalation of virions-carrying human aerosols represent the primary transmission pathway for airborne diseases including the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Relative to sneezing and coughing, non-symptomatic aerosol-producing activities such as speaking are highly understudied. The dispersions of aerosols from vocalization by a human subject are hereby quantified using high-speed particle image velocimetry. Syllables of different aerosol production rates were tested and compared to coughing. Results indicate aerosol productions and penetrations are not correlated. E.g. ‘ti’ and ‘ma’ have similar production rates but only ‘ti’ penetrated as far as coughs. All cases exhibited a rapidly penetrating “jet phase” followed by a slow “puff phase.” Immediate dilution of aerosols was prevented by vortex ring flow structures that concentrated particles toward the plume-front. A high-fidelity assessment of risks to exposure must account for aerosol production rate, penetration, plume direction and the prevailing air current.